2011
DOI: 10.1161/circimaging.110.961250
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Stress High-Pitch 128-Slice Dual-Source Myocardial Computed Tomography Perfusion for Imaging of Reversible Myocardial Ischemia

Abstract: Background-Coronary computed tomography angiography (CTA) enables accurate anatomic evaluation of coronary artery stenosis but lacks information about hemodynamic significance. The aim of this study was to evaluate 128-slice myocardial CT perfusion (CTP) imaging with adenosine stress using a high-pitch mode, in comparison with cardiac MRI (CMR). Methods and Results-Thirty-nine patients with intermediate to high coronary risk profile underwent adenosine stress 128-slice dual source CTP (128ϫ0.6 mm, 0.28 seconds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
1
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(78 citation statements)
references
References 22 publications
1
70
1
6
Order By: Relevance
“…Even though stress DECT-MPI is potentially superior to routine CTP for detecting perfusion defects, the diagnostic performance and increased value of stress DECT-MPI for detecting perfusion defects are limited and mainly involve only small pilot studies. Compared to the study by Feuchtner et al [11], the diagnostic performance of stress CVIA DECT-MPI is similar in the per-segment analysis but lower in the per-vessel analysis compared with routine CTP against CMR-MPI, particularly the lower specificity and PPV. Our results differ from Bettencourt et al [14], who reported that routine CTP showed 67% sensitivity and 95% specificity at the patient level and 55% sensitivity and 95% specificity at the vessel level compared with CMR-MPI for detecting perfusion defects.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…Even though stress DECT-MPI is potentially superior to routine CTP for detecting perfusion defects, the diagnostic performance and increased value of stress DECT-MPI for detecting perfusion defects are limited and mainly involve only small pilot studies. Compared to the study by Feuchtner et al [11], the diagnostic performance of stress CVIA DECT-MPI is similar in the per-segment analysis but lower in the per-vessel analysis compared with routine CTP against CMR-MPI, particularly the lower specificity and PPV. Our results differ from Bettencourt et al [14], who reported that routine CTP showed 67% sensitivity and 95% specificity at the patient level and 55% sensitivity and 95% specificity at the vessel level compared with CMR-MPI for detecting perfusion defects.…”
Section: Discussioncontrasting
confidence: 58%
“…Accordingly, combined ICA/ CMR-MPI is sufficient as a reference standard for collecting anatomical and physiological information regarding coronary stenosis. CTP has been widely investigated using various CT scanners, acquisition protocols, study populations, and reference standards and is considered a promising method for imaging myocardial ischemia, comparable to SPECT and CMR-MPI [7][8][9][10][11][12][13][14]. Bettencourt et al [14] demonstrated that CTP is globally inferior to CMR-MPI; however, integrating CTP and CCTA showed similar diagnostic performance to CMR-MPI using FFR as the reference standard for detecting hemodynamically significant CAD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many single and multicenter studies have validated the results of myocardial CTP against other modalities such as SPECT, CMR, PET, invasive coronary angiography (ICA) and invasive fractional flow reserve (FFR) (34)(35)(36)(37)(38)(39)(40)(41)(42). Most of these were performed in a limited number of patients and using different scanner generations, showing high sensitivity and negative predictive value, and moderate specificity and positive predictive value.…”
Section: Introductionmentioning
confidence: 99%